The Primacy of Multimodal Alignment in Converging on Shared Symbols for Novel Referents. Issue 3 (16th March 2022) - Rasenberg, Marlou; Özyürek, Asli; Bögels, Sara; Dingemanse, Mark
ABSTRACT: When people interact to establish shared symbols for novel objects or concepts, they often rely on multiple communicative modalities as well as on alignment (i.e., cross-participant repetition of communicative behavior). Yet these interactional resources have rarely been studied together, so little is known about if and how people combine multiple modalities in alignment to achieve joint reference. To investigate this, we systematically track the emergence of lexical and gestural alignment in a referential communication task with novel objects. Quantitative analyses reveal that people frequently use a combination of lexical and gestural alignment, and that such multimodal alignment tends to emerge earlier compared to unimodal alignment. Qualitative analyses of the interactional contexts in which alignment emerges reveal how people flexibly deploy lexical and gestural alignment in line with modality affordances and communicative needs.